PERAN LOGIKA UNTUK MEMBANGUN KEMAMPUAN SISWA SMPN 2 LABUAPI DALAM BERPIKIR KRITIS - Mutmainnah, Neneng; Lisatullaeli; Nurul Izzati; Ulfaunnisah; Zulfiya Ayunia Jaelani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking is the ability to analyze information, evaluate arguments, and make evidence-based decisions. This skill becomes crucial in the information age, where students face data streams that require proper filtering and interpretation (Brookfield, 2012). However, many students still struggle with systematic problem analysis, especially at the secondary school level. This research employs a qualitative approach with descriptive methods. The research location is SMPN 2 Labuapi, located on Jl.K.H. Dahlan, Perempuan, Labuapi District, West Lombok Regency, West Nusa Tenggara. Based on field observations, the inference learning process at SMPN 2 Labuapi is typically taught indirectly through subjects such as mathematics, science, and social studies. The learning logic is not explicit but is often applied within the context of related topics. The logic learning process at SMPN 2 Labuapi plays a vital role in developing students' critical thinking abilities. In this context, logic is not only implemented but also used as a tool underlying students' ability to analyze information, evaluate arguments, and make rational decisions. Proper implementation strategies, such as logical discussions and case studies, enable students not only to solve problems but also to enhance their analytical and evaluation skills.